Tratamento em duas fases na purificação de efluentes de lixiviados pela integração dos processos de eletrocoagulação e oxidação biológica - Pauli, Aline Roberta de (2018)
This work aims to remove efficiently organic and inorganic pollutants from a municipal sanitary landfill leachate effluent (SLLE) through of the integrated purification treatment application, composed by the electrocoagulation (ECP) and biological oxidation processes (BOP), looking for the drastic drop on the toxicity. In the first treatment phase, an ECP-based reactor was constructed consisting in a series of 6 aluminum electrode, providing an effective area of 350 cm2 and a useful volume of 1,0 L. In the framework of the response surface methodology (RSM), a 3³ complete factorial experimental design (CFED) at three levels of the three ECP important parameters: initial pH, electric current density (ECD) and electrolysis time (ET) was regarded. A set of responses related to the ECP treatment, such as, the reduction of color, turbidity, COD and iron concentration, was interpreted within the RSM. Additionally, the Analysis of Variance (ANOVA was applied to assess the quality of the second-order polynomial mathematical models that were adjusted to the CFED data. Keeping fixed the best ECP condition (pH and ECD) for the pollutant removals, a set of kinetic tests was carried out regarding a wide range of ET values. The toxicity of ECP treated samples was assessed by the application of bioassays based on the mortality level of the brine shrimp (Artemia salina) and the germination of Lactuca sativa seeds. The toxicity level was assessed by a statistical estimation of the median lethal concentration (LC50) through the application of bioassays with Artemia salina and Lactuca sativa. The biodegradability index by applying the Zahn Wellens test was also assessed. Keeping fixed the ECP condition for which was obtained the lowest toxicity and the highest biodegradability index, the second phase of treatment by BOP was performed. In this regard, a biological reactor with a useful volume of 3.5 L was adjusted to operate keeping fixed the condition of pH 7, temperature of 33 oC and dissolved oxygen of 50%. A relation food/microorganism of one was considered. After that, the residual ammonia in samples was completely removed applying the stripping method (air injection of 50 Lh-1). From the CFED data related to the first treatment phase, the best ECP condition was found by setting the pH at 5, ET at 120 min and ECD at 128.57 Am-2 for which was obtained the maximum removal of 99, 98, 68 e 99% for color, turbidity, COD and iron concentration, respectively. From the kinetic tests, it was possible to verify that the application of the ECP has actually reduced the SLLE toxicity being an ET of 5 min enough to achieve the minimum time required to obtain the lowest toxicity index (LC50 of 43%) that was found in both biotests. The highest biodegradability index was found when an ET value of 45 min. was regarded. The second POB treatment has showed a significant performance on removals of the organic parameters, with values of 95% and 89% for COD and DOC, respectively. Because of achieving an almost 100% removal of the ammoniacal nitrogen, the main result was the substantial improvement on the LC50 value about of 95%, as suggested by the A. salina biotest. Thus, although there were small amounts of pollutants after both treatments (PEC and POB), an almost total toxicity depletion.